Respuesta :
Answer:
[tex]52\frac{1}{4\\}[/tex] - [tex]49\frac{4}{9}[/tex] = [tex]\frac{101}{36}[/tex]
Step-by-step explanation:
First, we have to convert the mixed fractions to improper fractions
[tex]52\frac{1}{4\\}[/tex] = [tex]\frac{4 x 52 +1}{4}[/tex] = [tex]\frac{209}{4}[/tex]
[tex]49\frac{4}{9}[/tex] = [tex]\frac{9 x 49 + 4}{9}[/tex] = [tex]\frac{445}{9}[/tex]
[tex]\frac{209}{4}[/tex] - [tex]\frac{445}{9}[/tex] = [tex]\frac{1881}{36}[/tex] - [tex]\frac{1780}{36}[/tex] = [tex]\frac{101}{36}[/tex]
We cannot simplify [tex]\frac{101}{36}[/tex] so it is the final answer